Strategy, independence, and governance of state-owned enterprises in Asia - Henrique Schneider (Asian Development Bank Institute (ADBI), 2019)
New public management emphasizes the organizational and behavioral aspects of state-owned enterprises (SOEs). The main assumption is that, if governments constitute SOEs as "market" enterprises and allow their management to follow the logic of the "market," SOEs will become productive, innovative, and customer-oriented. This paper claims that, although new public management is a necessary condition, it is not sufficient for guiding (or reforming) SOEs. Strategic guidance from the owner (i.e. the state) as well as independence from the government have to complement it. The strategic guidance that the owner gives to an SOE has to address several areas of guidance. Ideally, it parallels the ownership strategies that are typical of more mature family enterprises. On the other hand, once the ownership strategy is in place, SOEs have to maintain their independence from the government, that is, its owners, to avoid co-option from political goals or short-term deviations from the strategy.
Keywords: H00; H11; M10; 330; SOE; governance; strategy; new public management; market imbalance; strategic management; competition